1990
DOI: 10.1128/jb.172.12.6803-6808.1990
|View full text |Cite
|
Sign up to set email alerts
|

Reverse gyrase, a hallmark of the hyperthermophilic archaebacteria

Abstract: Investigation of the presence of a reverse gyrase-like activity in archaebacteria revealed wide distribution of this activity in hyperthermophilic species, including methanogens and sulfur-dependent organisms. In contrast, no reverse gyrase activity was detected in mesophilic and moderately thermophilic organisms, which exhibited only an ATP-independent activity of DNA relaxation. These results suggest that the presence of reverse gyrase in archaebacteria is tightly linked to the high growth temperatures of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 38 publications
2
56
0
Order By: Relevance
“…This type I topoisomerase is the only enzyme unique to hyperthermophiles and the only known topoisomerase that can actively introduce positive superhelical twists into DNA (56,(65)(66)(67)(68).…”
Section: Resultsmentioning
confidence: 99%
“…This type I topoisomerase is the only enzyme unique to hyperthermophiles and the only known topoisomerase that can actively introduce positive superhelical twists into DNA (56,(65)(66)(67)(68).…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that overlinking could compensate for the effect of temperature on DNA structure (16). The enzyme is widely distributed in thermophilic archaea (6,8). The first reverse gyrase characterized was isolated from the hyperthermophilic archaeum Sulfolobus acidocaldarius (23,33).…”
mentioning
confidence: 99%
“…Reverse gyrase is the only topoisomerase known to overwind DNA. So far it has been found exclusively in hyperthermophiles, organisms that live above ϳ80°C (4,5). The role of the protein in vivo remains unclear (6); one suggestion is that it rewinds the DNA strands in regions of the chromosome that have opened up to allow transcription or replication (7).…”
mentioning
confidence: 99%